Testing the tehory, blessing or resource curse? The effect of natural resources on political violence in Africa - Han, Jiaxin; Feng, Fushen (Penerbit Universiti Kebangsaan Malaysia, 2023)
Political conflicts in Africa have intensified due to the competition for natural resources by various conflicting parties and their conflict intensification. Previous studies have shown that cell phone coverage plays a significant role in the occurrence of these conflicts. This paper explores the impact of oil reserves and diamond abundance on cell phone coverage in Africa. The authors also investigate how rebels are motivated by these resources to engage in conflicts. The Scobit model (Nagler 1994) is used to analyse the cases of unbalanced conflict, which is found to be more accurate than the Logistic model. The results indicate that diamond abundance is a resource blessing, while oil reserves lead to a resource curse. However, the latter finding needs to be more consistent across robustness checks, suggesting that the effects of different natural resources on African political conflicts remain debatable.